A constituição de uma questão sociocientífica em um grupo de professores: um processo polifônico de desvelamento da realidade concreta - Santos, Paulo Gabriel Franco dos; Carvalho, Washington Luiz Pacheco de [UNESP] (My University, 2013)
This article presents part of a broader research and seeks to elucidate the process of setting up a Socio-scientific Issue in a group of teachers at a public school. Assuming that a Socioscientific Issue must aggregate those involved in the educational process in situations of dialogue, argumentation and construction of a positioning, we understand that the recognition of the controversy or of the legitimacy of the theme in the context at stake is crucial to achieving the desired goals. Thus, starting from subsidies from the Critical Theory of Society, we characterize the process of setting up a Socio-scientific Issue among teachers as an exercise of unveiling the concrete reality, listing problematic, controversial and open to criticism aspects of Science and Technology. Thus, the Socio-scientific Issue is listed out in the group as soon as it is established a polyphonic dialogue where all participants stand, recognize the fertility of the themefor the intendededucational context and can speak of it with propriety.

Este artigo apresenta parte de uma pesquisa mais ampla e busca elucidar o processo de constituição de uma Questão Sociocientífica em um grupo de professores de uma Escola Pública. Partindo da premissa que uma Questão Sociocientífica deve agregar os envolvidos no processo educacional em situações de diálogo, argumentação e construção de posicionamento, entendemos que o reconhecimento da controvérsia ou da legitimidade do tema no contexto em questão é fundamental para alcançar os objetivos pretendidos. Sendo assim, partindo de subsídios da Teoria Crítica da Sociedade, caracterizamos o processo de constituição de uma Questão Sociocientífica entre professores como um exercício de desvelamento da realidade concreta, elencando aspectos problemáticos, controversos e passíveis de crítica da Ciência e da Tecnologia. Desse modo, a Questão Sociocientífica é elencada no grupo a partir do momento em que se estabelece um diálogo polifônico em que todos os participantes se posicionam, reconhecem a fertilidade do tema para o contexto educacional pretendido e conseguem falar dele com propriedade.
The establishment of a socio-scientific issue in a group of teachers: a polyphonic process of unveiling the concrete reality
Keywords: Socio-scientific issues; Formation of the subject; Group of teachers; Questões sociocientíficas; Formação do sujeito; Grupo de professores